2006
DOI: 10.3758/bf03192751
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sample size in controlled experiments: The CLAST rule

Abstract: Sequential rules are explored in the context of null hypothesis significance testing. Several studies have demonstrated that the fixed-sample stopping rule, in which the sample size used by researchers is determined in advance, is less practical and less efficient than sequential stopping rules. It is proposed that a sequential stopping rule called CLAST (composite limited adaptive sequential test) is a superior variant of COAST (composite open adaptive sequential test), a sequential rule proposed by Frick (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…vious research has shown that CLAST is more efficient, in terms of sample size and power, than is COAST and that it reflects more realistically the practice of experimental researchers, who obviously are not willing to incorporate an unlimited number of observations into their samples. The CLAST rule has been applied only to the one-tailed t test of mean differences with two matched samples and to the chi-square independence test for twofold contingency tables (Botella et al, 2006). The present work extends previous study on the efficiency of CLAST to multiple group statistical tests.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…vious research has shown that CLAST is more efficient, in terms of sample size and power, than is COAST and that it reflects more realistically the practice of experimental researchers, who obviously are not willing to incorporate an unlimited number of observations into their samples. The CLAST rule has been applied only to the one-tailed t test of mean differences with two matched samples and to the chi-square independence test for twofold contingency tables (Botella et al, 2006). The present work extends previous study on the efficiency of CLAST to multiple group statistical tests.…”
mentioning
confidence: 58%
“…Results of simulation studies indicated that COAST requires about 30% fewer observations than does FSR to achieve the same power. Botella, Ximénez, Revuelta, and Suero (2006) proposed the composite limited adaptive sequential test (CLAST), which is an extension of COAST. Pre-Extending the CLAST sequential rule to one-way ANOVA under group sampling CARMEN XIMÉNEZ AND JAVIER REVUELTA Universidad Autónoma de Madrid, Madrid, Spain Several studies have demonstrated that the fixed-sample stopping rule (FSR), in which the sample size is determined in advance, is less practical and efficient than are sequential-stopping rules.…”
mentioning
confidence: 99%
“…The present method is a variation of previous stopping rules originated by Frick (1998) and modified by Botella, Ximénez, Revuelta, and Suero (2006) and Ximénez and Revuelta (2007). These earlier methods did not control alpha at a constant level and were therefore less powerful than the variable-criteria SSR under certain conditions.…”
Section: P Smentioning
confidence: 99%
“…Other SSR approaches have been presented that are effective with large-sample techniques (Botella et al, 2006;Frick, 1998;Ximénez & Revuelta, 2007). Future research could extend the variable-criteria method to smaller effect sizes to assure users of a relatively constant observed alpha.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Botella, Ximénez, Revuelta, and Suero (2006) refined Frick's technique by adding a maximum sample size beyond which data collection would stop regardless of whether p still lies between α lower and α upper , and Fitts (2010) provides precise values for α lower and α upper for studies with small samples and large effects. Frick (1998), Botella et al (2006), or Fitts (2010 might be recommended for research situations in which an accurate power analysis is infeasible and when additional participants can be readily run individually or in small sets. Our technique might be recommended for situations in which an accurate power analysis can inform the size of N 1 or when multiple rounds of small dataset augmentation is less feasible.…”
Section: Maintaining P < 05 While Augmenting the Datasetmentioning
confidence: 99%